Comparison of percutaneous endoscopic discectomy and microendoscopic discectomy in treatment of symptomatic lumbar disc herniation: A protocol of cohort study - Hu, Yabin (Medicine (Baltimore), 2020)
BACKGROUND: Despite some researchers have compared the safety and effectiveness of percutaneous endoscopic discectomy (PED) and microendoscopic discectomy (MD) for the lumbar disc herniation; however, they got conflicting outcomes in several variables. Therefore, our aim was to clarify whether PED produces less surgical trauma and better clinical results than MD. METHODS: A single-center, retrospective cohort trial was conducted for the comparison of the safety and effectiveness between the MD and PED in the patients with lumbar disc herniation who received surgery from May 2016 to July 2018 in our hospital. The inclusion criteria for our investigation included: 1. age of 30 to 60 years; 2. preoperative CT and MRI scans revealed disc herniation; 3. conservative treatment was unsuccessful for at least 6 weeks; 4. patients with no former lumbar surgery history at same level. The follow-ups were performed 6 weeks, 3, 6, 12 and 24 months after the surgery. Numeric Rating Scale, Short-form 36, and Oswestry Disability Index, as well as complications were evaluated in our study. The software of SPSS Version 22.0 (IBM Corporation, Armonk, NY) was applied to analyze all the statistical data. When P is less than .05, the difference is significant in statistics. RESULTS: This protocol will provide a solid theoretical basis for exploring which technique is better in treatment of lumbar disc herniation. TRIAL REGISTRATION: This protocol was registered in Research Registry (researchregistry6005).